Assessment of tear secretion and tear film instability in cases with pterygium and normal subjects - Roka, Narayani; Shrestha, SP (Nepalese Journal of Ophthalmology, 2013)
Introduction: Dry eye is a common disorder affecting a significant percentage of the population. Materials and methods: This study is a prospective, hospital-based, case-controlled study conducted between January 2009 and May 2010. Seventy-six pterygium cases and 152 age-and- sex matched controls presenting to the OPD of Manipal Teaching Hospital were included. The TBUT Schirmer’s test and basal tear secretion were estimated in all patients. A TBUT of less than 10 seconds and a Schirmer’s test of less than 10 mm were considered abnormal. Results: Pterygium was bilateral in 15 (19.7 % ) and unilateral in 61 (80.3 %) patients. Ninety-two (92.1 %) pterygium patients reported either one or more of the six dry eye symptoms. Redness was the most common (67 %) symptom reported. The mean Schirmer’s test I, mean basal secretion and mean TBUT values were 16.19 mm, 10.01 mm and 10.56 seconds in pterygium cases and 20.22 mm,13.25 mm and 26.25 seconds in the control group respectively. There was a statistically significant difference in the dry eye results between the pterygium cases and the control group (p value < 0.05). The odds ratio between pterygium and dry eye was 3.28. Dry eye was present in 26 % of the normal patients and in 54 % of the pterygium cases. Conclusion: There is a strong relationship between dry eye and pterygium. Nepal J Ophthalmol 2013; 5(9):16-23 DOI: http://dx.doi.org/10.3126/nepjoph.v5i1.7816